(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article talks about feeding chickens based on the right diet. It is also said about the effect of adding vitamins and minerals to the diet of agricultural chickens on their productivity, brood of healthy offspring and growth. In addition, it is said about the unfavorable situations arising from the failure to provide the necessary vitamins and minerals in the diet of agricultural chickens.